KINERJA KEUANGAN PEMERINTAHAN DESA SEBELUM DAN SESUDAH PENGALOKASIAN DANA DESA DI TAHUN 2014 DAN TAHUN 2017 - Slamet Widodo (Pusat Kajian Anggaran, 2019)
An assessment of local government financial performance can be used as an input in the process of policy improvements in the future. The allocation of villages fund from National budget considered as momentum to review some financial indicator performance. This study measures village government financial ratios namely the ratio of independence, the ratio of revenues effectiveness, ratio of expenditure efficiency, ratio of operational expenditure, capital expenditure ratio, and ratio of revenues growth using secondary data from BPS survery results in 2014 and 2017. The analysis method used is One-way Anova. The purpose of the study was to see whether there was a change in the ratio before and after village funds allocation from National Budget. The results showed a significant difference between those ratios, except the efficiency ratio of village government spending.